Wybrane problemy restrukturyzacji podmiotów sektora komunalnego w Polsce - Zarzecki, Dariusz (Selected Issues of Restructuring Municipal Services in Poland, 2006)
The functioning of companies performing municipal services is subject of interest to both the academics and the practitioners. Municipal services should satisfy the needs of local communities and are an important part of the local market. Since 1990 in Poland we observe a self-government reform. The paper discusses the issue of organizational, legal and ownership transformations of municipal services, in particular concentrating on the advantages and disadvantages of holding companies and privatization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1124, s. 650-658